2018
DOI: 10.1007/s11010-018-3409-6
|View full text |Cite
|
Sign up to set email alerts
|

The utrophin–beta 2 syntrophin complex regulates adipocyte lipid droplet size independent of adipogenesis

Abstract: Utrophin is a widely expressed cytoskeleton protein and is associated with lipid droplets (LDs) in adipocytes. The scaffold protein beta 2 syntrophin (SNTB2) controls signaling events by recruiting distinct membrane and cytoskeletal proteins, and binds to utrophin. Here we show that SNTB2 forms a complex with utrophin in adipocytes. SNTB2 protein is strongly diminished when utrophin is low. Of note, knock-down of utrophin or SNTB2 enhances LD growth during adipogenesis. SNTB2 reduction has no effect on basal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…The expression of utrophin exhibits low tissue specificity [ 66 ]. Utrophin has been previously shown to regulate adipocyte droplet size [ 67 ]. Hence, the effect of stabilized utrophin on adipose tissues and insulin resistance could be an interesting research direction for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of utrophin exhibits low tissue specificity [ 66 ]. Utrophin has been previously shown to regulate adipocyte droplet size [ 67 ]. Hence, the effect of stabilized utrophin on adipose tissues and insulin resistance could be an interesting research direction for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of SNTA and SNTB2 on lipid droplet size in 3T3-L1 cells are independent of adipogenesis and expression of proteins mostly upregulated in differentiated adipocytes is not changed [11,12]. Thus, 3T3-L1 adipocytes with low SNTB2 have normal insulin-induced Akt phosphorylation [12]. Basal and β-adrenergic lipolysis are similar to controls while insulin stimulated antilipolytic effect is enhanced [12].…”
Section: Introductionmentioning
confidence: 90%
“…The adaptor proteins of the syntrophin family have been mostly studied in skeletal muscle where they are part of the dystrophin associated protein complex [10]. Alpha syntrophin (SNTA) and beta 2 syntrophin (SNTB2) are also expressed in adipocytes [11][12][13]. Recent work from our group showed that small lipid droplets are formed upon the knock down of SNTA during 3T3-L1 adipogenesis [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations